Caracterización agrosocioeconómica de los productores de Haba (Vicia Faba) involucrados en el proyecto Iniap Fiasa, semillas andinas en la región sierra. 2022 - 2023 - Vilca Guamaní, Marcia Estefanía (2023)
The research was carried out in the Sierra Region in Carchi and Imbabura provinces to broad bean (Vicia faba) producers, who are involved in the Andean Seeds project of the Agrobiodiversity, Seeds and Sustainable Agriculture Research Fund - FIASA together with the National Institute of Agricultural Research - INIAP, to characterize the Agrosocioeconomic situation of the 19 farmers through social, economic, and productive indicators, determining improvement strategies in these sectors that are dedicated to traditional agriculture, making use of the Rural and Participatory Diagnosis Methodology (DRP) that helps the research collect information through digital surveys prepared based on the needs and indicators to be studied, to carry out a census through the ODK-Collect application, getting results in Spss files for later coding in an Excel spreadsheet, where the results will be tabulated, codified, classified, and graphed, which will help the researcher analyze and use the valuation basis of the SARANDON methodology, for the value, codification, and integration of the social, economic, and productive indicators, on a scale within the range from 0 to 4, calculating the averages of each indicator, through amoeba graphs, the use of critical points that determines the strengths and weaknesses of the 19 broad bean producers is established, obtaining some results from the two provinces that indicate 68% of the people surveyed are women who are fully dedicated to agriculture and their home; therefore, the critical points of each indicator were four, with values of 0.00 to 1.68, which means, they are very bad values, so it is necessary to continue with the development of the INIAP FIASA project to establish government policies for the benefit of the agricultural sector and protection of the small bean farmer.